2009
DOI: 10.1007/s11249-009-9549-9
|View full text |Cite
|
Sign up to set email alerts
|

Macrotribological Studies of Poly(L-lysine)-graft-Poly(ethylene glycol) in Aqueous Glycerol Mixtures

Abstract: We have investigated the tribological properties of surfaces with adsorbed poly(L-lysine)-graft-poly(ethylene glycol) (PLL-g-PEG) sliding in aqueous glycerol solutions under different lubrication regimes. Glycerol is a polar, biocompatible liquid with a significantly higher viscosity than that of water. Macrotribological performance was investigated by means of pin-on-disk and mini-tractionmachine measurements in glycerol-PLL-g-PEG-aqueous buffer mixtures of varying compositions. Adsorption studies of PLL-g-PE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
41
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 65 publications
(44 citation statements)
references
References 32 publications
1
41
0
Order By: Relevance
“…In 2011, Nomura et al used an AFM-colloidal probe technique to show a transition in friction coefficient from µ < 0.001 at low shear rates (1-10 µm s -1 ) to µ ~ 0.01 at higher shear rates (10 3 µm s -1 ) between polystyrene brushes in toluene [52]. However, when the polymer brush interface is measured in a macro-tribometer, the resulting lubrication curve resembles the classic Stribeck curve at speeds above 1 mm s -1 [53]. Furthermore, at mN normal loads, the contact pressure at the polymer brush interface is orders of magnitude greater than the Gemini hydrogel interface, which provides an important point of distinction between the two materials [51].…”
Section: Resultsmentioning
confidence: 97%
“…In 2011, Nomura et al used an AFM-colloidal probe technique to show a transition in friction coefficient from µ < 0.001 at low shear rates (1-10 µm s -1 ) to µ ~ 0.01 at higher shear rates (10 3 µm s -1 ) between polystyrene brushes in toluene [52]. However, when the polymer brush interface is measured in a macro-tribometer, the resulting lubrication curve resembles the classic Stribeck curve at speeds above 1 mm s -1 [53]. Furthermore, at mN normal loads, the contact pressure at the polymer brush interface is orders of magnitude greater than the Gemini hydrogel interface, which provides an important point of distinction between the two materials [51].…”
Section: Resultsmentioning
confidence: 97%
“…Previous studies of aqueous lubrication of soft contacts involving PDMS showed clear transition of µ to increasing trend with increasing speed in high-speed regime [29,[36][37][38]. However, the base fluids in those studies were mixtures of water and corn syrup [36,37] or glycerol [38], and the viscosities of the fluids were a few orders of magnitude higher than that of water. Even with fluids with much higher viscosity, the transition to fluid-film lubrication was reported to occur from λ is ca.…”
Section: Hard Interfacesmentioning
confidence: 88%
“…They have been utilized in friction and wear studies as they are simple liquids without additives and their properties are well known. For glycerol, studies have been performed on the macroscale [86]. Dodecane, used with ZnS nanorod additives [25,29,33,46] and Au nano-objects dispersed in water [24,25,33], have resulted in reduced friction and wear on the micro/nanoscale.…”
Section: Choice Of Nano-objects and Liquids For This Studymentioning
confidence: 99%